Trigutomo, Effendi, Toenlioe PENGEMBANGAN PAKET PEMBELAJARAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS LEGO UNTUK MENINGKATKAN HASIL BELAJAR KELAS X SEMESTER 1 DI SMK-PP NEGERI KUPANG - Trigutomo, Wahyu Hadi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Learning package was developed based on the study of Learning Technology which uses the concept Dick, Carey & Carey (2009) that consist of ten steps: 1) Assess the need to identify the common goal of learning (Asessing needs to identify instructional goal), 2) Conduct analysis of general purpose learning (Conducting a goal instructional Analysis), 3) Analyze learners and the environment (Analyze learner and context), 4) Writing special purpose (Writing performance objectives), 5) Develop Instrument Rating (Developing Assessment instructional), 6) Develop a learning strategy (Developing and instructional strategy), 7) Developing learning materials (Developing instructional materials), 8) Design and conduct formative evaluation (Designing and conducting formative evaluation), 9) Revise learning (Revise Instruction), 10) Designing and implementing a summative evaluation (Design and conduct summative evaluation), and use learning strategies lego. The last stage design and conduct formative evaluation covers expert feedback content, design experts, and expert media, individual testing, piloting small groups, and field trials. At this stage of analysis and revision of the module teaching materials, student guides, teacher guides. The results of product development from some experts say feasible is as follows: 86.67% of subject matter experts and linguists 71.87%, amounting to 95% of design experts and media expert at 77.3%. While student learning outcomes showed an increase after using lego learning strategies to students, which originally contained 81.48% (Does not meet KKM), being 100% meets the KKM. Key words: Learning package development, Citizenship Education